Model for Medium-Term Municipal Waste Collection Optimisation - Hanczar, Paweł (Model decyzyjny optymalizacji zbiórki odpadów komunalnych w horyzoncie średnioterminowym, 2024)
Aim: The article presents the process of municipal waste management, with particular emphasis on the organization of waste collection, and discusses the objectives of waste management, the principles of operation in Poland and order in municipalities, and various approaches to organizing waste collection. The rest of the article presents a decision model for schedule generation based on mixed integer programming (MIP). This model aims to minimise the number of resources involved while meeting the requirements regarding the frequency of waste collection. One distinguishing characteristic of the proposed method is its premise that transport-related work should remain constant throughout the entire year, irrespective of holidays or days off. To achieve this, the model incorporates schedule substitutions which enable the strategic adjustment of schedules for collection dates affected by holidays, while preventing significant spikes in waste collection volume on those days. Methodology: The article proposes a decision model based on mixed integer programming (MIP), minimising the maximum amount of waste collected in one day. Results: Using the proposed decision-making model, tests were carried out on a set of 35 instances corresponding to real problems of preparing waste collection schedules in cities in the Lower Silesian Voivodeship. The test results confirmed the model’s efficiency. Implications and recommendations: The results obtained can be used in municipalities to create schedules and optimise the costs of municipal waste collection. Originality/value: The model proposal presented in the article contains unique elements, such as a decision model for optimising municipal waste collection over the year and substitutions in the context of the waste collection schedule. Introducing test case analysis adds value by demonstrating the practical application of the model.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 5, s. 92-100
Keywords: municipal waste schedule; decision-making model; optimisation; harmonogram odpadów komunalnych; model decyzyjny; optymalizacja